Monitoring and evaluation strategies: lessons learned from COVID-19 pandemic - Babalo Yekani; Bethuel Sibongiseni Ngcamu; Sareesha Pillay (Cogent Business & Management, 2024)
The COVID-19 pandemic presents unique challenges that necessitate a new approach to monitoring and evaluation (M&E) in local government. The culture of poor performance, high incompetency levels among employees and financial mismanagement – widely publicised in popular media in South Africa – prompted this study to investigate the effectiveness of M&E strategies. The study attempts to determine the effective M&E strategies in supporting two municipalities' response that extends beyond COVID-19. A transformative mixed methods approach was used for data collection and analysis of data. The targeted respondents were solely responsible for COVID-19 activities at the Nelson Mandela Bay Municipality and the Buffalo City Metropolitan Municipality. In-depth interviews were utilised to collect data from 13 senior municipal managers. A total of 191 questionnaires were despatched to municipal employees and 186 were returned, giving a 97% response rate. The findings depict ineffective M&E tools and inadequate organisational support to sustain best practices on municipal governance. The findings unearthed a linear relationship between the municipalities' leadership failure to implement a performance management system among its workforce and an exponential increase in COVID-19 cases and fatalities. This study attempts to make a valuable contribution in providing municipal employees with tailored work experience that will be relevant for future disasters similar to COVID-19, adding value to knowledge.
Keywords: 650; Digital management; implementation; intervention; monitoring and evaluation; municipalities; performance management